Crystallographic properties of fertilizer compounds - Frazier, A. W.; Dillard, E. F.; Thrasher, R. D.; Waerstad, K. R.; Hunter, S. R.; Kohler, J. J.; Scheib, R. M. (National Fertilizer and Environmental Research Center, Muscle Shoals, AL (United States), 1991)
This bulletin is a compilation of crystallographic data collected at NFERC on 450 fertilizer-related compounds. In TVA's fertilizer R and D program, petrographic examination, XRD, and infrared spectroscopy are combined with conventional chemical analysis methods in identifying the individual compounds that occur in fertilizer materials. This handbook brings together the results of these characterization studies and supplemental crystallographic data from the literature. It is in one-compound-per-page, loose-leaf format, ordered alphabetically by IUPAC name. Indexes provided include IUPAC name, formula, group, alternate formula, synonyms, x-ray data, optical data. Tables are given for solids, compounds in commercial MAP and DAP, and matrix materials in phosphate rock.